The Book of Common Prayer in Methodism: a Cherished Heritage or a Corrupting Influence? - Jérôme Grosclaude (Revue Française de Civilisation Britannique, 2017)
For a long time, Methodism had a complicated relation with its “Mother Church”, the Church of England, and the liturgical question provides a good illustration of this. Even though they separated from the Church of England in the 1790s, Wesleyan Methodists (the majority group) followed the instructions and practice of the founder, John Wesley, by making it compulsory to use the Book of Common Prayer for their offices, while allowing at the same time for impromptu prayers (also dear to their founder’s heart). Non-Wesleyans, on the contrary, eager to distinguish themselves from the detested Church of England, did not use a set form of worship for most of the 19th century and their services were generally improvised.After describing the (Wesleyan and non-Wesleyan) Methodist vision of the liturgy of the established Church in the 18th and 19th centuries, this article will study the reasons why the British Methodist Churches adopted set liturgies from the 1860s, and how they were created. Finally, we will see to what extent these 19th- and 20th- century rituals were indebted to the Book of Common Prayer.